Answer:
x = -3
Explanation:
You have the following equation:
![3(2x+4)=-6\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/3ucyfob1cia8a4mhpox1c3m1ebi2mcezbq.png)
you first you distribution property in order to eliminate the parenthesis:
![3*2x+3*4=-6\\\\6x+12=-6](https://img.qammunity.org/2021/formulas/mathematics/high-school/8hhokjytypjdrkp9q6t7tviscbb1sbtvbk.png)
next, you subtract 12 in both sides of the equation:
![6x+12-12=-6-12\\\\6x=-18](https://img.qammunity.org/2021/formulas/mathematics/high-school/u4x4qq407q72nbpugip15dhzz9acxlgrcb.png)
Finally, you divide the equation by 6 and simplify:
![(6x)/(6)=-(18)/(6)\\\\x=-3](https://img.qammunity.org/2021/formulas/mathematics/high-school/90pxp1urihnmam3p8ypr0xzk0dxh88cmvy.png)
hence, the solution to the equation is x = -3